The Possibilities for Developing the Tax Potential of the Constituent Entities of the Russian Federation - Olkhovik, Vladimir Vitalevich (Economy of Regions, 2019)
The problem of developing the tax potential of the constituent entities of the Russian Federation is crucial in the context of the country’s socio-economic instability. This instability results in the limited opportunities for the regional budgets to get financial support from the Federation. Combining the best practices of developing the tax potential with new author’s approaches and recommendations has allowed identifying the main ways to improve the fiscal policy of regional authorities. The article describes the opportunities and directions for further development of the tax potential of the Russian Federation entities in order to increase the level of their fiscal capacity. In particular, I focused on analysing the measures aimed at the extension of the existing tax base and improvement of the region′s investment climate for attracting potential taxpayers. The research methods include empirical and statistical research, synthesis of practical and theoretical materials, formal logic. I performed data processing and information systematization by applying cluster method, classification, comparative, logical and econometric analysis. In the context of the existing regional legislation, I identified the opportunities for the mobilization of tax revenues. A separate section is devoted to the implementation of the stimulating tax incentives and development of the integrated approach to its efficiency assessment. As for the prospects of improving the constituent entities’ investment attractiveness, the paper analyses opportunities and potential results for applying tax credit and differentiated tax rates. Moreover, the article examines the creation of funds for producing the import-substituting goods on the region′s territory. Based on the results of analysing the best regional practices in taxation and legislative framework of 85 entities of the Russian Federation, I developed proposals aimed at the development of the economy’s priority sectors. Particularly, they focus on attracting investments through establishing new models and forms of the state support of innovative and investment activities. Such proposals are especially relevant for the regions characterised by a low level of fiscal capacity and unbalanced budgets.